2008
DOI: 10.1007/s11064-008-9729-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiratory Dysfunction in Familiar Parkinsonism Associated with PINK1 Mutation

Abstract: In the present study mitochondrial respiratory function of fibroblasts from a patient affected by early-onset parkinsonism carrying the homozygous W437X nonsense mutation in the PINK1 gene has been thoroughly characterized. When compared with normal fibroblasts, the patient's fibroblast mitochondria exhibited a lower respiratory activity and a decreased respiratory control ratio with cellular ATP supply relying mainly on enhanced glycolytic production. The quantity, specific activity and subunit pattern of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 34 publications
5
66
0
Order By: Relevance
“…In agreement with other studies (Gandhi et al, 2009;Piccoli et al, 2008;Wood-Kaczmar et al, 2008), we did not observe differences in maximal activity for the OXPHOS complexes in PINK1-KD or PINK1-KO cells. However, we cannot exclude the possibility that the OXPHOS system might operate less efficiently in resting PINK1-deficient cells, thus explaining the depolarized .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies (Gandhi et al, 2009;Piccoli et al, 2008;Wood-Kaczmar et al, 2008), we did not observe differences in maximal activity for the OXPHOS complexes in PINK1-KD or PINK1-KO cells. However, we cannot exclude the possibility that the OXPHOS system might operate less efficiently in resting PINK1-deficient cells, thus explaining the depolarized .…”
Section: Discussionsupporting
confidence: 93%
“…Piccoli and colleagues [262]also performed studies on fibroblasts from a patient with a PINK1 mutation and observed a low mitochondrial respiratory activity and increased oxygen radical production due to complex I inhibition, demonstrating clinically what has been shown experimentally.…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 69%
“…Consistent with these findings in Drosophila, patients with PINK1 or PARKIN mutations have indistinguishable clinical features and also show mitochondrial defects (1,15). Recent studies also suggest that Pink1 and Parkin regulate mitochondrial functions in mammals (16)(17)(18)(19). These findings underscore the central importance of the Pink1/Parkin pathway in regulating mitochondrial integrity and function.…”
Section: Central Role Of Mitochondrial Function In Pd Pathogenesismentioning
confidence: 72%